(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The agile product development methodology is a series of concepts used for the creation of applications. In the creation of agile applications, strategies evolve by cooperation of self-organizing, cross-functional teams using suitable methods for their context. This paper provides principles that should be implemented in the agile product creation phase. Approximately 500 agile app engineers across the globe have engaged in the study. A questionnaire pertaining to the different protection practices to be implemented during each process of agile software creation was demanded in the survey. Based on this analysis, we have carried out the most effective and useful compliance practices that can be implemented across the multiple phases of agile software development. 80% of agile developers voted for initial preparation, which is an essential protection practice to be implemented during the pre-requirement process. Similarly, 75 per cent said that protection criteria during the requirement process, 95 per cent opted for risk analysis during the design phase, 80 per cent said that coding guidelines during the development phase, 62 per cent said that they defined, conducted and enforced safety checks during the testing phase, and 77 per cent said that the final safety check during the release phase would be integrated during the various agile software phases. The proposed analysis overcomes the problems of agile design and protection by offering a simple overview of the security practices implemented throughout the multiple phases of software growth. We have bridge-in, a protection difference between the conventional paradigm of waterfalls and the in-practice agile model of growth.